Biomechanical aspects of sports-related head injuries - Park, M. S.; Levy, M. L. (Physical Medicine & Rehabilitation Clinics of North America, 2009)
With the increased conditioning, size, and speed of professional athletes and the increase in individuals engaging in sports and recreational activities, there is potential for rising numbers of traumatic brain injuries in sports. Fortunately, parallel strides in basic research technology and improvements in computer and video technology have created a new era of discovery in the study of the biomechanical aspects of sports-related head injuries. Although prevention will always be the most important factor in reducing the incidence of sports-related traumatic brain injuries, ongoing studies will lead to the development of newer protective equipment, improved recognition and management of concussions on the field of play, and modification of rules and guidelines to make these activities safer and more enjoyable.